SUBSTANSI KEDAULATAN TUHAN DALAM KETATANEGARAAN REPUBLIK INDONESIA - Sukadi, Imam (Mimbar Keadilan, 2020)
AbstractThe Preamble of the 1945 Constitution of the Republic of Indonesia (URI NRI 1945) explains everything related to the basic, purpose, goals and ideals of the Indonesian nation in detail. The opening of the 1945 Constitution of the Republic of Indonesia occupies an important place in the state administration of the Republic of Indonesia. The substantive sovereignty of God in the constitutional system of the Republic of Indonesia is a very fundamental norm in the life of the nation and state. This is because that the substance of the sovereignty of God which originates in the Godhead is the life belief of the Indonesian people. For this reason, the substance of God's Sovereignty is included in various levels of life as a nation and state.Keywords: God's sovereignty; substanceAbstrakPembukaan Undang-Undang Dasar Negara Republik Indonesia 1945 (UUD NRI 1945) menjelaskan tentang segala sesuatu yang berkaitan dengan dasar, maksud, tujuan dan cita-cita bangsa Indonesia secara terperinci. Pembukaan UUD NRI 1945 menempati tempat yang penting dalam ketatanegaraan Republik Indonesia. Substansi kedaulatan Tuhan dalam system ketatanegaraan Republik Indonesia merupakan norma yang sangat fundamental dalam kehidupan berbangsa dan bernegara. Hal ini dikarenakan bahwa substansi kedaulatan tuhan yang bersumber pada Ketuhanan Yang Maha Esa adalah sebagai keyakinan hidup bangsa Indonesia. Untuk itu substansi Kedaulatan Tuhan masuk dalam tataran berbagai lini kehidupan berbangsa dan bernegara.Kata kunci: kedaulatan Tuhan; substansi